INFLUÊNCIA DOS GRUPOS DE PRESSÃO NO PROCESSO DE ELABORAÇÃO DA LEI DE BIOSSEGURANÇA E SEUS DESDOBRAMENTOS - Alexandre Augusto Alves Guedes (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2017)
This article analyzes the acting of Favorable and Contraries Pressure Groups for diffusion of Genetically Modified Organisms (GMOs) in the process of elaboration and discussion of Biosafety Law (Law 11.105/05) at the National Congress. It is argued the role played by each of these groups to the Theory of Groups. We are presented the favorable and contrary Pressure Groups as well as the participation of other stakeholders in the process. Subsequently, it's presented how the development of preparation process and voting of the Biosafety Law occurred, as well as the participation of pressure groups in such process. Groups gains and losses are pointed out in the ten years of existence of the law and it is concluded that despite the shocks between them have been important to balance the text of Law, with both having their main demands attended, Favorable Groups obtained, along these ten years, large domination in the approval of their claims in the Commission's guidelines of the National Biosafety Technical Commission (CTNBio) without any major intervention by the National Biosafety Council (CNBS).